2019
DOI: 10.1186/s13059-019-1731-2
|View full text |Cite
|
Sign up to set email alerts
|

Cold stress induces enhanced chromatin accessibility and bivalent histone modifications H3K4me3 and H3K27me3 of active genes in potato

Abstract: Background Cold stress can greatly affect plant growth and development. Plants have developed special systems to respond to and tolerate cold stress. While plant scientists have discovered numerous genes involved in responses to cold stress, few studies have been dedicated to investigation of genome-wide chromatin dynamics induced by cold or other abiotic stresses. Results Genomic regions containing active cis -regulatory DNA elements can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
111
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 82 publications
12
111
1
Order By: Relevance
“…In general, our analysis indicated that cold acclimation had a strong influence on the 437 expression of the selected epigenetics-related genes. This is in agreement with the finding 438 that cold stress enhanced the accessibility of chromatin and bivalent histone modifications of 439 active genes in potato (Zeng et al, 2019 It is interesting to note that several members of both families of demethylases displayed an 460 upregulation during cold acclimation before decreasing until 4 h Deacc followed by an 461 increase until 12 h Deacc before returning to the initial NA gene expression levels after 24 h 462…”
supporting
confidence: 85%
“…In general, our analysis indicated that cold acclimation had a strong influence on the 437 expression of the selected epigenetics-related genes. This is in agreement with the finding 438 that cold stress enhanced the accessibility of chromatin and bivalent histone modifications of 439 active genes in potato (Zeng et al, 2019 It is interesting to note that several members of both families of demethylases displayed an 460 upregulation during cold acclimation before decreasing until 4 h Deacc followed by an 461 increase until 12 h Deacc before returning to the initial NA gene expression levels after 24 h 462…”
supporting
confidence: 85%
“…In contrast to H2A.Z, H3K4me3 is generally not recognized as playing a negative role in gene expression. Studies in a variety of plant species and tissues have examined the change in genic levels of H3K4me3 in response to environmental stressors (Tsuji et al, 2006, Sokol et al, 2007, Kim et al, 2008, Van Dijk et al, 2010, Jaskiewicz et al, 2011, Zeng et al, 2019). These studies generally reported increases in H3K4me3 at genes up-regulated by stress.…”
Section: Discussionmentioning
confidence: 99%
“…These studies generally reported increases in H3K4me3 at genes up-regulated by stress. However, most of the studies examined relatively small numbers of genes, and the genome-level studies that compared average H3K4me3 genic profiles between control and stressed samples actually found substantial decreases in 5’ localization of H3K4me3 in response to stress (Zong et al, 2013, Zeng et al, 2019). We observed a similar effect when comparing the H3K4me3 profiles for all PCG between control and Pi deficiency conditions (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the heart of this regulation is the chaperone activity of the cold shock protein cspA and its 5'UTR that acts as a thermosensor (Giuliodori et al, 2010) and auto-regulates its own abundance in a temperature-dependent way . In plants, cold adaptation is more complex, involving temperature-induced adjustments of the chromatin (Zeng et al, 2019;Park et al, 2018), transcriptional (Nagano et al, 2019), pre-mRNA processing (Calixto et al, 2018), post-transcriptional and posttranslational landscapes (Zhu, 2016). The transcriptional response to cold acclimatization in plants is beginning to be unraveled and entire signaling networks such as the C-repeat binding transcription factor (CBFs) regulon have been exposed (Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%